Ramadan Fasting and NCDs-Example of the Diabetes - Bencharif, Meriem; Sersar, Ibrahim; Bentaleb, Maroua; Boutata, Fatima Zohra; Benabbas, Youcef (Frontiers in Nutrition, 2022)
Although Ramadan lasts only for 1 month each year, it can be accompanied by significant changes in: both energy and nutritional intake; in the diet composition; in the working hours; and the usual way of life. The majority of practitioners consume two meals, one after sunset (Iftar) and one before dawn (Sohor). During this month, it is also an opportunity to share a meal with family and friends, a period of highly intensified socialization. In parallel with the nutritional changes brought about by this unique pattern of fasting in Ramadan, other metabolic and physiological changes may occur, such as fluctuations in body weight and/or disturbance in the quantity and quality of the sleep-wake circadian rhythm. In the verses of the Qur'an, the exemption from fasting in certain situations such as illness is clearly stated. Despite this religious tolerance, many faithful who are eligible for the exemption observe the fast of Ramadan either for the spiritual aspect it provides by performing it, by religious guilt or to mark a normalization in the Muslim community for fear of the gaze of others. The world is experiencing an increase in the emergence of non-communicable diseases (NCDs); leading cause of the global mortality. Environmental and behavioral risk factors related to lifestyle, such as smoking, excessive alcohol consumption, unhealthy diet, and sedentarity have a causal association with NCDs. Other factors, such as genetic and physiological factors may also be associated (overweight, high blood pressure, dyslipidemia). Diabetes is one of the highest prevalent NCDs in the world and it continues increasing year by year. This chronic disease can lead to significant potential complications (degenerative, dermatological, and acute) to the patient's health. This requires an individual and appropriate care, both dietetic and therapeutic and over the long term will at best make it possible to sensitize the diabetic patient to the adverse effects related to his disease and thus improve its quality of life. Performing the Fast of Ramadan for a diabetic is a common situation. Diabetes is the only chronic disease widely studied in relation to Ramadan fasting. In the literature, many studies have investigated the effects of Ramadan intermittent fasting on diabetic patients. This article aims to provide a general overview and highlight if there are many effect of Ramadan fasting on diabetes, as an example of a NCDs.